Francoist repression in Spain and the crime of genocide - Kazyrytski, Leanid (Criminology & criminal justice, 2022)
This article describes the characteristics and scale of Francoist repression in Spain and analyses the potential interpretation of the mass killings of people with leftist ideology as an act of genocide in accordance with the provisions of international law. Focus is placed on the difficulties associated with the inclusion of political groups in the category of genocide victims, and the possibility of a broader interpretation of this categorization is defended. Furthermore, the present study emphasizes the influence of the positivist trend on the configuration of Francoist criminal policy and provides evidence that allows Francoist repression to be considered as genocide in full accordance with international law.